Initiating Entrepreneurship to Improve Health amongst People in Lio Village during The COVID-19 Pandemic: A Qualitative Study - Triastari, Stella K; Chandra, Angelina Patricia; Wibisono, Andito M; Friska, Dewi (UI Scholars Hub, 2022)
Community development in Lio Village performed by Faculty of Medicine Universitas Indonesia students aimed to improve the health status of villagers. Because economy correlates with health, an economic intervention may increase the health status of the people. Based on this, an entrepreneurship program was initiated as a part of a community development program. This study is qualitative study that was conducted between July 2020 and February 2021. The intervention consisted of asynchronous webinar sessions, workshops, and business competition. Data were gathered from post-test questionnaires through a Google form. The winners were chosen according to the business ideas and given prizes. Then, a follow-up interview was conducted to measure the benefits of the intervention. For the results, more than 50% of the participants understood the theory by answering correct questions in the post-evaluation forms. The participants also reported feeling happier and having better mental health. Of the 88 medical students who volunteered in the event, 78.2% felt a tremendously beneficial experience of community empowerment and 21.8% felt they have experienced community empowerment. In conclusion, remote-online community development intervention may be a solution during the COVID-19 pandemic. By acknowledging the importance of the economic aspect to health and improving aspects that influence health holistically, both economic and health states of the people may be improved.